ANALISIS RESPONS UMKM DAN KONTEN KREATOR TERHADAP KEBIJAKAN SOCIAL COMMERCE LEWAT PERATURAN MENTERI PERDAGANGAN NOMOR 31 TAHUN 2023 - Nathania Alwi Ramdhani; Imron Musthofa (Jurnal Ekonomi & Bisnis, 2023)
Social commerce services are online shopping platforms that combine with social media. There are positive and negative responses to the development of social commerce. Many are affected by social commerce. Many MSMEs and markets that market products offline have been forced to close down. The decline in turnover they obtained was due to not being able to compete with imported goods. Imported products enter social commerce at low prices. These products also enter the country without permits. The government suspects that social commerce has carried out predatory pricing. As a result, local products cannot compete because of the significant price gap. Besides that, people certainly prefer products with more affordable prices. The revision of the Minister of Trade's Regulation on social commerce has created pros and cons in society. Because there are also many elements that feel they benefit from social commerce. Especially content creators who use promotional features and MSMEs who have built businesses from this platform. The Minister of Trade revised regulation Number 31 of 2023 to create a middle ground for prosperity between offline and online services.